Parenting Rights After Divorce Positive Legal Perspectives and Islamic Law (Study of Lawang Agung Village, Kedurang District, South Bengkulu) (JURNAL HUKUM SEHASEN, 2021)
Humans are destined to live in pairs, which then the relationship between a man and a woman is bound in a marriage bond. It is based on Article 1 of Law Number 1 of 1974 concerning Marriage (Law No. 1 of 1974). This type of research is a qualitative approach. This type of research is categorized as field research, namely research carried out in the arena or field of the occurrence of symptoms. This study uses the correlation method, namely the method by connecting the selected and explained variables and aims to examine the extent to which the variables in one factor are related to other variables. 3. Child custody due to divorce according to law Positive views on child custody cases are not only a dispute between the interests of the plaintiff and the defendant but especially the interests of the child itself. The child in this case is a small child who is not yet mumayyiz (not yet 12 years old), then the interests of the child are considered to be the realm of public law, meaning that they are in the interests of the community and the state.